2011
DOI: 10.1111/j.1369-1600.2011.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cocaine‐induced locomotor sensitization in rats sustaining genetic or pharmacologic antagonism of ghrelin receptors

Abstract: Systemic infusions of the orexigenic peptide ghrelin (GHR) increase dopamine levels within the nucleus accumbens and augment cocaine stimulated locomotion and conditioned place preference in rats; observations that suggest an important role for ghrelin and GHR receptors (GHR-Rs) in drug reinforcement. In the present studies, we examined the development of cocaine locomotor sensitization in rats sustaining either pharmacologic antagonism or genetic ablation of GHR-Rs. In a pharmacologic study, adult male rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 45 publications
(63 reference statements)
3
36
1
Order By: Relevance
“…This is in line with the finding that GHS-R1a antagonism reduced drug-induced locomotor activity, 40,41 although central administration of ghrelin has been reported both to decrease 42 as well as increase 43 locomotor activity. In addition to the reduction in total RWA, rats with knockdown of GHS-R1a in DMH also exhibited a decrease in normalized FAA.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the finding that GHS-R1a antagonism reduced drug-induced locomotor activity, 40,41 although central administration of ghrelin has been reported both to decrease 42 as well as increase 43 locomotor activity. In addition to the reduction in total RWA, rats with knockdown of GHS-R1a in DMH also exhibited a decrease in normalized FAA.…”
Section: Discussionsupporting
confidence: 89%
“…The findings that the cholinergic–dopaminergic reward link is activated by pharmacological‐induced hyperghrelinemia (Jerlhag, 2008; Jerlhag et al., 2012) and that elevated ghrelin levels associated with craving (Addolorato et al., 2006; Koopmann et al., 2012; Leggio et al., 2012), may imply that high plasma levels of ghrelin may be needed for reward interactions. Supportively, animal studies show that hyperghrelinemia is associated with cocaine seeking and that peripheral ghrelin administration augments the cocaine‐induced conditioned place preference and locomotor stimulation (Clifford et al., 2012; Davis et al., 2007; Tessari et al., 2007; Wellman et al., 2005, 2012). Conclusively, future studies on the role of peripheral versus central ghrelin in relation to alcohol reward, intake, and craving are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Using animal models, studies have shown that administration of ghrelin can increase ethanol intake, while ghrelin antagonism reduces ethanol intake (Jerlhag et al, 2009). In addition, ghrelin antagonists have been shown to significantly reduce the behavioral and physiological effects of cocaine (Clifford et al, 2012), amphetamine (Jerlhag et al, 2010), and nicotine (Wellman et al, 2011; Jerlhag and Engel, 2011). In agreement with pharmacological studies, GHSR knockout mice show reduced voluntary ethanol intake and diminished ethanol-induced conditioned place preference (Jerlhag et al, 2009).…”
Section: Introductionmentioning
confidence: 99%